PERANCANGAN SISTEM INFORMASI BUKU TABUNGAN MENGGUNAKAN ORACLE APPLICATION DEVELOPMENT FRAMEWORK PT. ASURANSI SINARMAS - Getsemani Salisa Margaretha; Magdalena Ariance Ineke Pakereng (Politeknik Bisnis Indonesia, 2022)
A bank book is something that is needed by a customer, both a company and an individual. This is because the function of the bank book itself is as a system that records details of the entry and exit of money in the passbook, checking balances, monthly reports for incoming deposits, and so on. so that it is not uncommon for many well-known companies in Indonesia and abroad to create systems that design a company's financial records, such as P. Asuransi Sinarmas who also designs a bank book system with the tools used are Oracle Java Application Development Framework (oracle). ADF) and Oracle MySQL as data storage. Oracle is widely used by companies because it has several advantages in the amount of data it handles is very large, processes data quickly and accurately has a good ability to perform server clusters and database system management, can restore databases, and is multi-platform, can be used on other operating systems such as Mac and Linux.